Ways of preventing oxidative damage to meat pates - Zhadko, Maryna; Topchiy, Oksana (My University, 2018)
The search for a technically simple, cheap and, at the same time, an effective way to prevent oxidation and increase the shelf life of meat products, including pates, remains relevant.
Keywords: кафедра технології м’яса і м’ясних продуктів; ways to prevent oxidation; meat pâtés; extension of shelf life; продовження терміну придатності; способи запобігання окисленню; м’ясні паштети